The Royal Naval Dockyard in Bermuda: Use of a novel biological indicator and historical photographs for measuring local sea-level rise. (November 2022) - Rouja, Philippe M.; Schneider, Craig W.; Rissolo, Dominique; Blasco, Steve M.; Petrovic, Vid; Lo, Eric; Lightbourne, Mandellas A.; Tucker, Wendy S.; Kuester, Falko
The authors explore a novel interdisciplinary approach to researching, collecting and communicating local site-specific data on recent sea-level rise using persistent black-zone biotic levels evident on historical coastal stone structures by a stable community of cyanobacteria (blue-green algae) at the Royal Naval Dockyard in Bermuda. Photographs taken at the Dockyard in 1870, 2007 and 2017 show an upward shift in this living cyanobacterial community. A spatio-temporal digital twin computed from historical and contemporary photo assets was created to test the viability of these black-zone lines as a proxy for sea-level-rise measurements in Bermuda. Black-zone cyanobacteria are highly sensitive to sea-level rise and, over long timescales, comparative imagery of black zones could present a proper indicator of average sea-level rise.